Handbook of pulping and papermaking - Biermann, Christopher J. (Academic Press, 1996)
In its Second Edition, Handbook of Pulping and Papermaking is a comprehensive reference for industry and academia. The book offers a concise yet thorough introduction to the process of papermaking from the production of wood chips to the final testing and use of the paper product. The author has updated the extensive bibliography, providing the reader with easy access to the pulp and paper literature. The book emphasizes principles and concepts behind papermaking, detailing both the physical and chemical processes. Key Features * A comprehensive introduction to the physical and chemical processes in pulping and papermaking * Contains an extensive annotated bibliography * Includes 12 pages of color plates.